2016
DOI: 10.1042/bst20160027
|View full text |Cite
|
Sign up to set email alerts
|

The varied functions of aluminium-activated malate transporters–much more than aluminium resistance

Abstract: The ALMT (aluminium-activated malate transporter) family comprises a functionally diverse but structurally similar group of ion channels. They are found ubiquitously in plant species, expressed throughout different tissues, and located in either the plasma membrane or tonoplast. The first family member identified was TaALMT1, discovered in wheat root tips, which was found to be involved in aluminium resistance by means of malate exudation into the soil. However, since this discovery other family members have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
(66 reference statements)
2
27
0
Order By: Relevance
“…Subsequently, ALMT genes were identified from many plants and proved to be related to many physiological processes in plant, such as Al detoxification, mineral nutrition, stomatal movement, fruit acidity, seed development, and other abiotic stress [24,[38][39][40]. It was found that there were 14 ALMT members in Arabidopsis thaliana, 16 members in Fragaria vesca, 9 members in rice, 27 members in Pyrus bretschneideri, 25 members in Malus domestica, 25 members in Prunus mume [22,23,38,41]. However, little is known to the ALMT genes in rubber trees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, ALMT genes were identified from many plants and proved to be related to many physiological processes in plant, such as Al detoxification, mineral nutrition, stomatal movement, fruit acidity, seed development, and other abiotic stress [24,[38][39][40]. It was found that there were 14 ALMT members in Arabidopsis thaliana, 16 members in Fragaria vesca, 9 members in rice, 27 members in Pyrus bretschneideri, 25 members in Malus domestica, 25 members in Prunus mume [22,23,38,41]. However, little is known to the ALMT genes in rubber trees.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding malate transporters have been found in many plant species, such as Arabidopsis (AtALMT1), rape (BnALMT1, BnALMT2), rye (ScALMT1), and soybean (GmALMT1) [18][19][20][21]. Furthermore, more studies showed that members of the ALMT family were not only associated with Al resistance but also participated in other physiological processes, including stomatal movement, cellular signaling, cell expansion, nutrients acquisition, fruit flavor regulation, and GABA (γ-aminobutyric acid) signaling [22][23][24]. Nevertheless, the ALMT family member has not been reported in the rubber trees.…”
Section: Introductionmentioning
confidence: 99%
“…Anion transport via ALMTs is an important and well accepted mechanism for signalling (Bouche et al, 2003a; Roberts, 2007; Pineros et al, 2008; Dreyer et al, 2013; Ligaba et al, 2013; Ramesh et al, 2015), stomatal pore regulation (Meyer et al, 2010; Roelfsema et al, 2012; De Angeli et al, 2013; Kollist et al, 2014; Palmer et al, 2016), phosphorous nutrition (Liang et al, 2013; Balzergue et al, 2017) and for providing tolerance to Al 3+ at low pH (Delhaize and Ryan, 1995; Sasaki T, 2004; Zhang et al, 2008; Ryan et al, 2011). We have demonstrated that TaALMT1 is able to facilitate GABA efflux and influx at very high rates.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 additional genes encoding OA transporters have been linked with Al resistance in other species including most important crops (Table 1). These OA transporters are encoded by two gene families: the Al-activated malate transporter (ALMT) family encodes anion channels that release malate from cells, and the multidrug and toxic compound extrusion (MATE) family encodes co-transporters that release citrate from cells (Takanashi et al, 2014;Palmer et al, 2016;Sharma et al, 2016). Some of the genes in Table 1 have a strong genetic and physiological association with Al resistance, but for others, the links remain correlative and further confirmation is required.…”
Section: The Increased Expression Of Certain Organic Anion Transportementioning
confidence: 99%